Blade Runner and Memory Devices: Reconsidering the Interrelations between the Body, Technology, and Enhancement. Issue 1 (1st March 2016) - Fukushima, Masato
Abstract : This article provides a theoretical basis for reconsidering current discussions on the relation between the body, technology, and enhancement. Using the conceptual distinctions of model 1 (which is based on the notion of the unmediated body and technology) and model 2 (which begins with the techno-body complex) types of understanding of enhancement, and emphasizing a reappraisal of Vygotskian tradition for demarcating the role of mediating signs and tools in psychology, I compare two existing controversies regarding enhancement: the various disputes concerning technological enhancement in elite sports competition, and the recent controversy about using digital technology for memory enhancement. The framework used for this comparison is the concept of regime, consisting of the following layers of criteria: (1) the nature of each specific domain where enhancement is defined and measured, (2) the structure of agencies or institutions concerned with the issue, and (3) the underlying value that implicitly affords such an effort toward enhancing our capacity. With regard to the elite sports regime, the focus is rather tightly structured, whereas for memory enhancement, the controversy is diffuse and widely distributed. The sharp contrast in these two regimes is shown to be deeply related to the different types of understanding enhancement. In conclusion, this article suggests that the discussion on enhancement is a probe for the larger system of values, which inevitably forces us to reexamine our own values with the help of the tentative conceptual scheme provided herein.